2017
DOI: 10.5603/gp.a2017.0058
|View full text |Cite
|
Sign up to set email alerts
|

The utility of maternal mean platelet volume levels for early onset neonatal sepsis prediction of term infants

Abstract: Objectives: This study is aimed to evaluate the role of maternal mean platelet volume (MPV) levels for antenatal prediction marker of early onset neonatal sepsis in term infants born to mothers who have low infection risk. Material and methods:A total of 62 pregnant women who gave birth in our hospital and whose neonates were admitted to a third level Neonatal Intensive Care Unit due to confirmed neonatal sepsis between January 2010 and May 2016 were selected as a study group. Within the same period, 68 women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…A microorganism infection causes an inflammatory reaction, which results in increased total leukocyte and neutrophil numbers (29,30). In addition, those with sepsis experienced a considerable enhancement in immature neutrophil count and I/T ratio than controls, which reveals the crucial role of CBC with a differential in the identification of EOS (P = 0.0001); this was also proven by Cekmez et al (31). Our results were not in line with those of Can et al (26), that reported no statistically significant differences in the I/T ratio between the EOS group and the control group.…”
Section: Discussionsupporting
confidence: 52%
“…A microorganism infection causes an inflammatory reaction, which results in increased total leukocyte and neutrophil numbers (29,30). In addition, those with sepsis experienced a considerable enhancement in immature neutrophil count and I/T ratio than controls, which reveals the crucial role of CBC with a differential in the identification of EOS (P = 0.0001); this was also proven by Cekmez et al (31). Our results were not in line with those of Can et al (26), that reported no statistically significant differences in the I/T ratio between the EOS group and the control group.…”
Section: Discussionsupporting
confidence: 52%
“…A fetal weight prediction model is created without the need for complex calculations and is also able to show the exact weight of the fetus. [17] In this study, the sensitivity and specificity of two-dimensional color Doppler ultrasound in the diagnosis of fetal developmental abnormalities were 78.38% and 82.60%, respectively, while the sensitivity and specificity of 4D color Doppler ultrasound in the diagnosis of fetal developmental abnormalities were 81.5% and 83.43%, respectively. The results showed that the application of 4D ultrasound scanning with GE-E10 equipment could effectively improve the accuracy of fetal weight estimation.…”
Section: Discussionmentioning
confidence: 57%
“…The role of maternal mean platelet volume levels for the prediction early onset neonatal sepsis in term infants were also studied by Yasemin Cekmez, Merve Dizdar et al, [10] and found that MPV levels were statistically higher in the study group of mothers with infection than the control group. It is easy to predict the probability of sepsis in infants born to mothers who has clinical findings of chorioamnionitis, and other systemic infections.…”
Section: Discussionmentioning
confidence: 98%